TYPOLOGY OF EXPRESSION DRAWING WORKS IN SDN 02 WONOTIRTO KECAMATAN BULU KABUPATEN TEMANGGUNG (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2017)
The steps to make sense of the typology of expression drawing works of the children can be initiated by interpreting the characters of the lines, colors, shapes, and the themes or the concept of mind visualized onto certain medium. The characters can be interpreted based on psychological concepts of colors, lines, and shapes so that we can find out the typology of the child’s work. Typology of children’s works based on the types and characters of artworks is closely correlated to the skills and the creativity of a child. The observation on the children’s works were made comprehensively, not only on the end-results, but also including implementation process undertaken gradually, in planned way, and continuously to acquire the illustration of the progress of the students’ learning process. Observation on the expression drawing was aimed at finding out the children’s interests, talents, and skill to respond to the social environment. The observation was made deeply in order to find out the emotional degree and motor skill they have, the children’s interest in colors and shapes, as well as the factors influencing the creation of the expression drawing. The research was made deeply in order to find out the emotional degree and motor skill of the children, their interests in colors and shapes, as well as the factors influencing the expression drawing creation. The research was made by qualitative method through the heuristic approach on the whole population of SDN 02 Wonotirto including the teachers and the students. The study acquired several findings, i.e. students’ expression drawing resulted in SDN 02 Wonotirto manifested into three typologies including haptic, visual, and mixed types and the visual one dominated. Concept of children expression drawing creation was dominated more by external factors acquired from the teachers, students, the social environments and television. The children’s creativity inhibitor is that their ability to respond was limited to the direct responses to the themes around them and they tent to imitate them.